Fast track to Adobe Captivate 6 - Horsley, Anita; Safari eBooks ([S.l.] : Packt Pub., 2013)
"This video tutorial series is for educators, corporate training professionals, and training specialists with limited programming capabilities who want to create product demos, application simulations, and soft skill and compliance training. In order to participate in the practical portion of this course, it is highly recommended that you download Adobe Captivate 6 before beginning the course. You can download a free trial version here: https://www.adobe.com/cfusion/tdrc/index.cfm?product=captivate&loc=en_us. Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. Fast Track to Adobe Captivate 6 is aimed at helping new users wrap their head around the basics of using Adobe Captivate 6. Discover how to use Adobe Captivate 6 to create interactive online learning content using realistic demonstrations and practical materials to develop a course from start to finish."--Resource description page.
Title from resource description page (viewed Oct. 04, 2013).
Presenter, Anita Horsley.
Keywords: Captivate (Electronic resource); Computer animation; Multimedia communications; Programmed instruction; Multimedia communications -- Programmed instruction; Electronic books